Bioefficacy of combination insecticide, buprofezin + deltamethrin against leaf folder and planthoppers infesting rice - Sontakke, B K; Mohapatra, L N (Indian Journal of Plant Protection, 2020)
Bioefficacy of combination insecticide, buprofezin + deltamethrin (5.65 % + 0.72 %), a product of Meghamani Organics Ltd., Ahmedabad was evaluated at two doses 62.5 +0.78 g a.i./ha and 75.0+0.94 g a.i./ha along with the available market samples against leaf folder and plant hoppers (BPH and WBPH) infesting rice under irrigated conditions at Central Farm, Orissa University of Agriculture and Technology, Bhubaneswar during Kharif seasons of 2009 and 2010. The results revealed that combination of buprofezin and deltamethrin in both the doses provided an effective control of leaf folder and planthoppers with higher grain yield.